Relative condition factor, length-weight relationship and sex ratio of copper mahseer, Neolissochilus hexagonolepis (McClelland, 1839) from Tamor River, Nepal (Our Nature, 2018)
The present investigation was carried out for establishing the length weight relationship and to enumerate the relative condition factor and the sex ratio of Neolissochilus hexagonolepis from Tamor River, Nepal. Altogether 198 fishes were investigated from December 2014 till the end of November 2016. The sex ratio of the fish was found to be in the ratio of 1:1.2 with female dominating the catch for most parts of the year. Analysis of t-test showed a highly significant relationship (p˂0.05) between length and weight for male, female and sexes pooled. The fish was found to show isometric growth pattern with exponential value (b) equal to 2.962 for sexes pooled. The mean value of Fulton's condition factor (K) for sexes pooled was found to be 1.29 ± 0.49 giving the indication that the general well being of the fish was good. Sudden increase in the value of relative condition factor (Kn) in the size group 30-33 cm in male and 42-45 cm in female indicated their length range during which they showed the sign of maturation for the first time. Steep fall in the value of 'Kn' in size groups 33-36 cm onwards in male and 45-48 cm in female indicated their length range at spent phase.